MEANING RELATIONS BETWEEN IDEAS IN EXPOSITION TEXTS BY GRADE X STUDENTS OF SUNAN KALIJOGO JABUNG - Wardani, Dewi Tugas Kusuma (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This research focuses on the types of meaning relations and grammatical units that relate between ideas. This research uses a qualitative approach. The source of data in this research is the exposition text by students of class X SMA Sunan Kalijogo Jabung. The paradigmatic meaning relations found are four kinds. Grammatical units that relate between ideas found five types.